Assessing the Costs of Intravenous Push Waste in Intraoperative Areas Through Observation: A Multi-site Study - John B. Hertig; Les Louden; Blake Shay; Armando Soto; Garrett Robbins; Tatyana Kornilova; Prachi Arora (Drugs - Real World Outcomes)
Abstract Introduction The costs associated with proper disposal, management, and regulatory compliance of controlled substances in healthcare systems are substantial. In the context of the current opioid crisis, and given the high abuse potential of controlled substances, it is imperative that waste is minimized and waste procedures are followed to ensure safe disposal of controlled substances. This study aims to quantify the costs associated with fentanyl, hydromorphone, morphine, midazolam, and ketamine waste in intraoperative areas through a multi-site observational analysis. Methods The study used an observational design across various hospital procedural and post-procedural units in the Southwest Florida region of the United States. Automated and non-automated workflows for wasting controlled substances were compared. As with a previous study conducted by Hertig et al., waste was evaluated as (1) the quantity (mg/μg) of medication disposed defined as ‘pharmaceutical waste’ or ‘product waste’ (PW); and (2) workforce time associated with the waste disposal process defined as ‘workforce time waste’ (WTW). Secondary measures include workforce costs associated with the waste disposal process. The product waste analysis was conducted between October and December 2023. The workforce time waste analysis was examined over a 10-day period in January and February 2024. A yearly extrapolation model was applied to cost data. Results The findings revealed substantial costs linked to both PW and WTW, emphasizing the financial burden of controlled substance waste. Study data validated previous literature describing the extent of fentanyl, hydromorphone, and morphine waste while documenting significant amounts of midazolam and ketamine waste. The combined annual waste cost for the two study hospitals was estimated at US$56,557, with workforce time accounting for 36%–50% of this total cost. Conclusion This study provides vital insights into the financial and operational impact of medication waste in procedural and post-procedural areas, supporting ongoing efforts to minimize waste, ensuring the safe and effective use of controlled substances. Future research should explore the impact of medication waste across diverse healthcare settings and the cost implications associated with pharmacy professionals in the waste compliance process.